Directionality in Aesthetic Judgments and Performance Evaluation: Sport Judges and Laypeople Compared - Loffing, Florian; Nickel, Stefanie; Hagemann, Norbert (Frontiers in Psychology, 2017)
Left-to-right readers are assumed to demonstrate a left-to-right bias in aesthetic preferences and performance evaluation. Here we tested the hypothesis that such bias occurs in left-to-right reading laypeople and gymnastic judges (n = 48 each) when asked to select the more beautiful image from a picture pair showing gymnastic or non-gymnastic actions (Experiment 1) and to evaluate videos of gymnasts’ balance beam performances (Experiment 2). Overall, laypeople demonstrated a stronger left-to-right bias than judges. Unlike judges, laypeople rated images with left-to-right trajectory as more beautiful than content-wise identical images with right-to-left trajectory (Exp. 1). Also, laypeople tended to award slightly more points to videos showing left-to-right as opposed to right-to-left oriented actions (Exp. 2); however, in contrast to initial predictions the effect was weak and statistically unreliable. Collectively, judges, when considered as a group, seem less prone to directional bias than laypeople, thus tentatively suggesting that directionality may be an issue for unskilled but not for skilled judging. Possible mechanisms underlying the skill effect in Exp. 1 and the absence of clear bias in Exp. 2 are discussed alongside propositions for a broadening of perspectives in future research.